2006
DOI: 10.1099/vir.0.81794-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of synthetic peptides from heptad-repeat domains of herpes simplex virus type 1 glycoproteins H and B

Abstract: Human herpesviruses enter cells by fusion of their own membrane with a cellular membrane through the concerted action of multiple viral proteins and cellular receptors. Two conserved viral glycoproteins, gB and gH, are required for herpes simplex virus type 1 (HSV-1)-mediated membrane fusion, but little is known of how these proteins cooperate during entry. Both glycoproteins were shown to contain heptad repeat (HR) sequences predicted to form a-helical coiled coils, and the inhibitory activity against infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
68
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 55 publications
1
68
1
Order By: Relevance
“…Although previous studies reported that gH displays hallmarks of fusion proteins (26)(27)(28)(29), the crystal structure of the HSV-2 gH ectodomain bound to gL bears no similarity to any known viral fusogen (30). Nonetheless, both gB and gH may possess fusogenic capabilities, as each alone can promote membrane fusion during nuclear egress (31).…”
mentioning
confidence: 94%
“…Although previous studies reported that gH displays hallmarks of fusion proteins (26)(27)(28)(29), the crystal structure of the HSV-2 gH ectodomain bound to gL bears no similarity to any known viral fusogen (30). Nonetheless, both gB and gH may possess fusogenic capabilities, as each alone can promote membrane fusion during nuclear egress (31).…”
mentioning
confidence: 94%
“…This complex is a major target of virus-neutralizing antibodies in several herpesviruses (17,43), emphasizing its role in virus entry. It has been proposed that gH has features characteristic of class I viral fusogens (14)(15)(16). However, the recently published structures of HSV-2 and EBV gH/gL (9,39) suggested that these proteins do not likely act as cofusogen but rather regulate fusion by gB.…”
mentioning
confidence: 99%
“…It has been proposed that HSV-1 gH has features characteristic of class I viral fusogens, such as putative heptad repeats and fusion peptides (6,(9)(10)(11). Also, peptides matching the sequence of gH can interact with lipids and/or induce the fusion of lipid vesicles (4,5,8).…”
mentioning
confidence: 99%